1999
DOI: 10.1136/adc.80.6.517
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of discontinuing growth hormone treatment

Abstract: Aims-To evaluate the eVects of discontinuing growth hormone (GH) treatment on energy expenditure and body composition, which might help predict those most likely to benefit from early reintroduction of GH treatment in young adult life. Methods-Body composition was calculated from skinfold thicknesses and dual energy x ray absorptometry (DXA). Resting metabolic rate (RMR) and whole body bone mineral content (BMC) were also measured. Measurements were made before stopping treatment, at discontinuation of GH trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Many studies have demonstrated deficits in somatic and metabolic maturation in GH-deficient individuals untreated during the transition period [1-4,6-17]. However, the determination of precisely which patients require ongoing GH therapy has been less clear, as many patients treated for childhood GHD do not fulfill diagnostic criteria for adult GHD after completion of linear growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated deficits in somatic and metabolic maturation in GH-deficient individuals untreated during the transition period [1-4,6-17]. However, the determination of precisely which patients require ongoing GH therapy has been less clear, as many patients treated for childhood GHD do not fulfill diagnostic criteria for adult GHD after completion of linear growth.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, GH potentially could be continued uninterrupted through the transition period (with appropriate dosage adjustment) to avoid the adverse changes in body composition, lipid profile, and cardiac function that may develop following discontinuation of GH [1-4,6-17] . Furthermore, patient care could potentially be improved by providing the family with a clear expectation at the initiation of childhood treatment, of the likelihood that GH treatment will be required in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone can increase resting energy expenditure [21] and modulates thyroid hormone metabolism by increasing activation of thyroxine to tri-iodothyronine [22]. It increases lean mass and reduces body fat [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies specifically addressing the benefits of GH replacement therapy in adolescents who have finished growing, considered to be in transition, have so far yielded somewhat conflicting results. A small cohort of 11 adolescent subjects with GH deficiency had a decrease in resting energy expenditure and an increase in adiposity within a few weeks after discontinuation of GH, effects sustained for 1 yr of observation and not detected in healthy controls (30). Vahl et al (4) studied 19 adolescents with childhood-onset GH deficiency at the time of discontinuation of treatment, followed for 1 yr on either placebo or GH and then another year on GH in all subjects.…”
Section: Body Compositionmentioning
confidence: 97%